Management of Selected Insect Pests with Pest-attractive Plants in Organic Tangerine Farming Systems in Northern Thailand - Senaratne L. Ranamukhaarachchi*, Chomchuan Boonrahong and (Recent Research in Science and Technology, 2010)
Tangerine is a cash crop in Thailand which is heavily vulnerable to insect pests. Heavy use of pesticides has severely affected environment and people’s health. This study was conducted to assess the biological pest management potential using pest attractive plant species to reduce the use of highly toxic pesticides and to improve the quality of the product and environment health. Sixteen suspected weed species were allowed to grow with tangerine and tested their pest attractiveness for four key insect pests for 12 weeks. From this study, three weeds [viz. goat weed (Ageratum conyzoides), Siam weed (Chromolaena odorata), and buffalo grass (Paspalum conjugatum)] were identified for further studies and tested together with cowpea (Vigna unguiculata), rice (Oryza sativa) and chilly pepper (Capsicum frutescens) based on farmers’ information in an organically grown tangerine farm. All plant species tested attracted citrus leafminers and citrus whiteflies as tangerine pests, and among the natural enemies, ladybird beetle and weaver ants. Asian citrus psyllids were attracted on buffalo grass, rice and chilly peppers, while black citrus aphids were attracted on Siam weed and chilly peppers only. The two natural enemies namely, green lacewings and tropical orb weaver spiders were attracted by Siam weed, buffalo grass and rice, which together with chilly peppers attracted tropical orb weaver. The Asian citrus psyllids and citrus whitefly damage on tangerine associated with chilly peppers was minor-moderate, minor with Siam weed, buffalo grass and rice, but not observed on tangerine associated with goat weed and cowpea. Black citrus aphid damage was minor on tangerine associated with all plants, except cowpea. Citrus leafminer damage was between minor-moderate in tangerine associated with Siam weed and cowpea, and above moderate-heavy with rest of the plant species. These results show that pest attraction varies with plant species and by selecting plant species in a mixed stand with cowpea and chilly peppers and by leaving these weeds can help managed tangerine pests and minimize use of toxic pesticides.